Murshid Contestation: Betwen IktisÄbÄ« and MinhÄh IlÄhiyyah - Anam, Syariful (Teosofia: Indonesian Journal of Islamic Mysticism, 2017)
A murshid has a great duty and responsibility to conduct suluk formation (spiritual journey) to his students. So that the murshid are also required to have adequate competence and qualifications, in order to carry out their duties and functions. The functions and duties of the murshid in the tarekat (the path of Islamic Mysticsm) are very important, because only a murshid has the qualifications, abilities and expertise that can carry out their functions correctly, correctly and run accordingly. So that this aspect of ability and expertise will later be discussed as a discussion of the qualifications of a murshid in the tarekat. What is the actual qualification of murshid in the tarekat and what is its function in that proximity. This research is a type of field research. That is with the object of the study of the murshid of the Naqsabandiyyah Khalidiyyah in the sub-district of wedung precisely in the village of Jetak (KH. Abdul Haq), Buko village (KH. Ali Hafidz and KH. Ahmad Dalhar) and Mutih village (KH. Mansur Sanusi). The author collects data using the method of field observation, interviews and documentation. Next, the writer analyzes the data using descriptive analysis and understands the meaning. The results of the study stated that the murshid of the Naqsabandiyyah Khalidiyah tarekat in Wedung District argued that between the murshid tarekat function is hifdz sanad, talqin, tawassul, rabitah, tawajjuh and irsyad. While the qualifications to become murshid, among others; First, a murshid must be someone who is pious and amil bi ilmihi. The second has a clean heart, Third, has completed or khatam dzikir and khalwat tarekat (riyadhah), Fourth, has a murshid sanad, even though the inqitha'us sanad is from its predecessor murshid but continued with other murshid teachers in the same type of tarekat. Fifth, get permission from the murshid teacher. Sixth, knowing the wisdom behind all acts of worship (if possible). Through this research, the author recommends the need to study more about the wider range of murshid tarekat qualifications and not just the Naqsabandiyyah Khalidiyyah tarekat Indonesia. Thus, the form of the murshid qualifications will be found in several comprehensive tarekat